Development Of A Robust Blind Digital Video Watermarking Algorithm Using Discrete Wavelet Transform - Al-Deen, Ahmed A. Baha'a (2007)

(untitled)
Video watermarking technology enables us to hide an imperceptible, robust, and secure data in digital or analog video. This data can be used for tracking, fingerprinting, copyright infringement detection or any other application that requires some hidden data. Video watermarking can be achieved by either applying still image technologies to each frame of the movie or by using dedicated methods which exploit inherent features of the video sequence. There is a complex trade-off between three requirements in digital watermarking: robustness against noise and attacks, imperceptibility or invisibility, and capacity, which represent the amount of data, i.e., the number of bits encoded by the watermark. However, these three requirements conflict with each other. Increasing the watermark strength makes the system more robust but unfortunately decreases the perceptual quality. Whereas, increasing the capacity of the watermark decreases the robustness.In the production chain, video compression is usually applied before broadcasting or before transferring the video to other devices. In order to be robust against format conversions, the watermark has to be inserted before compression. Therefore, uncompressed video format has been used in the research undertaken. On the other hand, a random key is used to choose the frames to be watermarked to increase the security level of the algorithm and discourage piracy. The aim of this research is to develop a video watermarking algorithm to embed a binary image inside the uncoded video stream that acts as a logo. A mid-band discrete wavelet transform coefficients of the selected frames are chosen to be the hosted region in the frequency domain. An inverse transformation should be taken in order to get the desired watermarked video shot. In extraction process the watermark is extracted from the marked video directly without access to the original video. The experiment results showed that the proposed scheme provides better quality watermarked videos in term of watermark invisibility to human eyes. Results also indicated that obtaining average peak signal to noise ratio (PSNR) equals 41.59dB as compared with 38.48dB in the case of direct embedding. In addition, the scheme is robust against video processing operations, such as MPEG compression which could be successfully recovered. In conclusion, modifying the wavelet coefficients depending only on the logo object's pixels highly improve the invisibility and at the same time providing a good robustness level.